Low-field NMR investigations on dynamics of crude oil confined into nanoporous silica rods and white powder - Ok, Salim (Frontiers in Chemistry, 2023)
In the present study, to mimic the natural confinement of crude oils, model experiments are conducted with crude oils having different physical properties and maltenes of parent crude oils without asphaltenes confined into engineered nanoporous silica rods with pore diameters of 2.5 and 10.0 nm and white powdered nanoporous silica with pore diameters of 2.5 and 4.0 nm. This will help with suggesting potential treatments for enhancing crude oil recovery. Low-field nuclear magnetic resonance (LF-NMR) relaxometry has been applied to achieve this goal. The nanoporous proxies resemble real-life nanoporous rocks of reservoirs. The dynamics of confined crude oils with different oAPI gravity deviate from bulk dynamics, and deviation changes depending on the oAPI gravity. This suggests that treatments must be decided appropriately before crude oil production. Similar treatments could be applied for light and medium-heavy crude oils. Mathematical analysis of NMR relaxation curves of confined crude oils with different fractions of SARA (saturates, aromatics, resins, asphaltenes) indicates that the conventional SARA approach needs a better definition for the confined state of matter. The NMR relaxation behavior of confined maltenes shows that resin molecules might act like saturates in natural confinement with various scale pores from nano to micro and even macro, or aromatics might show resin-like behaviors. Confinement of brine and a light crude oil into white powdered nanoporous silica proxies demonstrates that brine could be utilized along with some additives such as nanoparticles for oil recovery. Therefore, these issues must be evaluated in deciding the proper treatments for crude oil production.